2022
DOI: 10.3390/pharmaceutics15010148
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cationic Dendrimers and Their Complexes with microRNAs on Immunocompetent Cells

Abstract: Short regulatory oligonucleotides are considered prospective tools for immunotherapy. However, they require an adequate carrier to deliver potential therapeutics into immune cells. Herein, we explore the potential of polycationic dendrimers as carriers for microRNAs in peripheral blood mononuclear cells of healthy donors. As an oligonucleotide cargo, we use a synthetic mimic and an inhibitor of miR-155, an important factor in the development and functioning of immunocompetent cells. Dendrimers bind microRNAs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…The complexes were incubated in the dark for 15 min at room temperature and used for subsequent work (dendriplexes were prepared anew for each experiment). Physicochemical characteristics of complexes obtained (hydrodynamic diameter 35–45 nm; PDI 0.21–0.25; zeta potential +14 mV for AE2G3-miR complexes, +1.5 mV for BDEF33-miR complexes) were in accordance with those observed earlier [ 41 ].…”
Section: Methodssupporting
confidence: 89%
See 2 more Smart Citations
“…The complexes were incubated in the dark for 15 min at room temperature and used for subsequent work (dendriplexes were prepared anew for each experiment). Physicochemical characteristics of complexes obtained (hydrodynamic diameter 35–45 nm; PDI 0.21–0.25; zeta potential +14 mV for AE2G3-miR complexes, +1.5 mV for BDEF33-miR complexes) were in accordance with those observed earlier [ 41 ].…”
Section: Methodssupporting
confidence: 89%
“…As carriers, we have chosen polycationic phosphorus and carbosilane dendrimers that we had already proven to be efficient carriers of therapeutic nucleic acids into both tumor [ 38 , 67 ] and immunocompetent cells [ 25 , 31 , 33 , 41 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among other approaches, noteworthy is the acetylation of dendrimers, which leads to neutralization of the surface amine cationic charge, which causes dendrimer toxicity by disrupting biological membranes. It is important to note that the very process of dendrimer complexation with nucleic acids (including short oligonucleotides, miRNAs, RNA, and DNA vaccines) reduces the charge of the complex and the cytotoxicity of the dendrimer [176][177][178]. Thus, dendrimer toxicity issues can be successfully addressed using chemical and biophysical approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus dendrimers or dendrons, due to their good biocompatibility and the presence of a large number of modifiable sites on the surface and branches, have been shown to have excellent performance in drug delivery, , gene transfection , and drug active per se . Their relatively convenient synthesis method also allows the development of various nanoparticulate systems to tackle a wide range of diseases. Our earlier work has shown that phosphorus dendrimers bearing pyrrolidinium or piperidinium on their surface can be used for gene delivery to treat breast cancer .…”
Section: Introductionmentioning
confidence: 99%